PROMOSI KESEHATAN TENTANG PENCEGAHAN STUNTING PADA MASYARAKAT DI DESA KALIBURU - Khofifah Indarwati; Niluh Putu Evvy Rossanty 2 (Pusat Riset dan Inovasi Nasional, 2023)
Stunting is still a national health problem. In the case of stunting in Kaliburu Village, there were 19 children identified as stunting symptoms. Lack of mother's knowledge about fulfilling good nutrition is one of the factors causing stunting. Health promotion with counseling methods is considered effective in increasing public knowledge. This activity was carried out at one of the Posyandu cadres in Kaliburu Village on October 5, 2022, with a total of 19 participants consisting of parents of children identified as stunting. The method used in this health promotion activity is in the form of counseling, discussion, and question and answer. The use of counseling methods has proven to be effective in areas with limited learning media, so that participants can increase their knowledge about the causes, effects, and ways to prevent stunting and correct wrong perceptions about stunting.